Reproducing musical instrument components from manufacturers' technical drawings using 3D printing: Boosey & Hawkes as a case study. Issue 5 (20th October 2019) - Cottrell, Stephen; Howell, Jocelyn
Abstract : This paper demonstrates how component musical instrument parts can be recreated from manufacturers' technical drawings using 3D printing. While the application of this technology is not new, previous approaches have usually involved Computer Tomography scanning of extant models. Instead we used surviving technical drawings of clarinet mouthpieces originally manufactured by Boosey & Hawkes. We demonstrated that this non-invasive technique can be used to 3D print musical component parts if the original plans survive, even when extant parts do not. We also demonstrated through qualitative feedback from professional musicians that hand finishing of 3D printed mouthpieces remains essential for skilled performers.